2020
DOI: 10.3390/biomedicines8040073
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone-Calcitriol Combination Enhanced Cytotoxicity of Cisplatin in Ovarian and Endometrial Cancer Cells In Vitro

Abstract: Initially, patients that respond to cisplatin (DDP) treatment later relapse and develop chemoresistance. Agents that enhance DDP effectiveness will have a significant impact on cancer treatment. We have shown pronounced inhibitory effects of the progesterone-calcitriol combination on endometrial and ovarian cancer cell growth. Here, we examined whether and how progesterone-calcitriol combination potentiates DDP anti-tumor effects in cancer cells. Ovarian and endometrial cancer cells treated with various concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Obviously, PI3K/AKT and MAPK/ERK pathways are important components that regulate cancer cell proliferation, migration, and metastasis. In addition, many studies have shown that DDP resistance is related to altered cancer cell signaling pathways, including PI3K/AKT and MAPK/ERK pathways (24,25). Therefore, we investigated whether the effect of CB in promoting DDP sensitivity is related to PI3K/AKT and MAPK/ERK signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, PI3K/AKT and MAPK/ERK pathways are important components that regulate cancer cell proliferation, migration, and metastasis. In addition, many studies have shown that DDP resistance is related to altered cancer cell signaling pathways, including PI3K/AKT and MAPK/ERK pathways (24,25). Therefore, we investigated whether the effect of CB in promoting DDP sensitivity is related to PI3K/AKT and MAPK/ERK signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, calcitriol significantly inhibited the expression of NLRP3 inflammasome-related genes and IL-1β production in hyperosmotic stress (HS)-exposed cells ( Dai et al, 2019 ). In addition, the combination of progesterone and calcitriol significantly inhibited the growth of endometrial and ovarian cancer cells ( Paucarmayta et al, 2020 ). The results of our study showed that calcitriol levels in the B. fragilis group were significantly higher than those in the control group, and vaginal administration also significantly altered steroid and steroid hormone biosynthesis according to KEGG.…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro study on ovarian cancer cells revealed that a combination of progesterone, calcitriol, and cisplatin significantly enhanced the effectiveness of anticancer therapy [55]. The triple-drug combination was observed to promote apoptosis by downregulating the expression of BCL2 and PARP-1, upregulating caspase-3 and BAX, and inhibiting the PI3K/AKT and MAPK/ERK signaling pathways [55].…”
Section: Ovarian Cancermentioning
confidence: 99%
“…An in vitro study on ovarian cancer cells revealed that a combination of progesterone, calcitriol, and cisplatin significantly enhanced the effectiveness of anticancer therapy [55]. The triple-drug combination was observed to promote apoptosis by downregulating the expression of BCL2 and PARP-1, upregulating caspase-3 and BAX, and inhibiting the PI3K/AKT and MAPK/ERK signaling pathways [55]. Additionally, a reduction in the expression of SMAD2/3, ABC transporters (ABCG1 and ABCG2), and the multidrug resistance protein-1 (MDR-1) was associated with increased responsiveness to treatment [55].…”
Section: Ovarian Cancermentioning
confidence: 99%
See 1 more Smart Citation